Feast your eyes - Wright, Brittany (New York : Little, Brown and Company, 2017)
Artist Brittany Wright was stuck in a job she didn't love and needed a new creative project to stay happy -- so she learned to cook. Inspired by the effortless beauty of her ingredients -- fresh fruits, vegetables, and more -- she created the hugely popular Instagram hashtag #foodgradients to showcase the splendor of nature's edible rainbows. The vivid photographs in this book capture the diversity and beauty of the foods we love to eat, from heirloom tomatoes and hot peppers to ripe strawberries and frosted cupcakes. Inside, revel in the vivid neons of your favorite candies, the rich color of freshly picked greens, and the gorgeous shades you can even find in a single cup of coffee. Each exquisite, neatly ordered photograph is a pleasure to get lost in. With a sleek, minimalist design and more than a hundred high-quality photographs, Feast Your Eyes is a celebration of the earth's bounty, a breath of fresh air for the busy mind, and an inspiration for everyone looking for joy in the simple things.
Keywords: PHOTOGRAPHY OF FOOD